Protection of Indigenous Peoples the Owner of Traditional Cultural Expressions in Indonesia (Global Journal of Human-Social Science, 2017)
Indonesia has 33 provinces with different ethnics and cultures that the presence is highly valuable.
Keywords: protection; indigenous peoples; owner; traditional cultural expressions; Indonesia